2010
DOI: 10.1186/1471-2164-11-384
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing and comparative analysis of cucumber flowers with different sex types

Abstract: BackgroundCucumber, Cucumis sativus L., is an economically and nutritionally important crop of the Cucurbitaceae family and has long served as a primary model system for sex determination studies. Recently, the sequencing of its whole genome has been completed. However, transcriptome information of this species is still scarce, with a total of around 8,000 Expressed Sequence Tag (EST) and mRNA sequences currently available in GenBank. In order to gain more insights into molecular mechanisms of plant sex determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
146
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(162 citation statements)
references
References 70 publications
(84 reference statements)
11
146
0
4
Order By: Relevance
“…The duplicated region contains the ACS1 (Csa6G496450) gene as well as Csa6G496950 (a gene of unknown function), Csa6G496960 (encoding a truncated MYB transcription factor), and part of Csa6G496970 (encoding a branched-chain amino acid aminotransferase) ( Figure 3D). The previously reported differentially expressed genes between female and male flowers, such as auxin-related and short-chain dehydrogenase or reductase genes related to the development of unisexual flowers (Huang et al, 2009;Guo et al, 2010), were not found in this region; thus, they are likely downstream floweringrelated genes. To further confirm the association between the CNV and gynoecy, we resequenced six additional gynoecious lines (GCA07, GCA09, HAU106, IVF204, HAU107, and SJ08).…”
Section: Genesis Of the F Locusmentioning
confidence: 99%
“…The duplicated region contains the ACS1 (Csa6G496450) gene as well as Csa6G496950 (a gene of unknown function), Csa6G496960 (encoding a truncated MYB transcription factor), and part of Csa6G496970 (encoding a branched-chain amino acid aminotransferase) ( Figure 3D). The previously reported differentially expressed genes between female and male flowers, such as auxin-related and short-chain dehydrogenase or reductase genes related to the development of unisexual flowers (Huang et al, 2009;Guo et al, 2010), were not found in this region; thus, they are likely downstream floweringrelated genes. To further confirm the association between the CNV and gynoecy, we resequenced six additional gynoecious lines (GCA07, GCA09, HAU106, IVF204, HAU107, and SJ08).…”
Section: Genesis Of the F Locusmentioning
confidence: 99%
“…Innovations in sequencing RNA (RNA-seq) led to the generation of millions of short sequence reads of cDNAs derived from poly(A)-enriched mRNA from different tissues or conditions in a cost effective manner, which were then mapped onto unique locations on the genome to predict AS events (Wang et al, 2009a;Filichkin et al, 2010;Hallegger et al, 2010;Marquez et al, 2012). This has been used to analyze the extent of AS and to identify novel introns and splice variants in Arabidopsis (Filichkin et al, 2010;Marquez et al, 2012;Syed et al, 2012), rice (Oryza sativa; Zhang et al, 2010b), cucumber (Cucumis sativus; Guo et al, 2010), grape (Vitis vinifera; Zenoni et al, 2010), and Brachypodium distachyon (Walters et al, 2013). These studies have revealed that up to 60% of introncontaining genes are alternatively spliced.…”
Section: Spliceosome Composition and Assemblymentioning
confidence: 99%
“…Expressed sequence tags (ESTs) are important for studying the structure and function of functional genome. ESTs have played significant roles in accelerating gene discovery, improving genome annotation, elucidating phylogenetic relationships, facilitating breeding programs by providing SSR and SNP markers, analyzing large-scale gene expression and rapidly identifying transcripts involved in specific biological processes [6]. During the last few years, EST analysis of P. yezoensis has been conducted in many laboratories [7][8][9], and approximately 22000 ESTs have been deposited into the dbEST database at NCBI.…”
mentioning
confidence: 99%